Methylation of HPV16 and EPB41L3 in oral gargles and the detection of early and late oropharyngeal cancer. (26th May 2022) - Dickey, Brittney L.; Nedjai, Belinda; Preece, Matthew D.; Schell, Michael J.; Boulware, David; Whiting, Junmin; Sirak, Bradley; Abrahamsen, Martha; Isaacs‐Soriano, Kimberly A.; Kennedy, Kayoko; Chung, Christine H.; Giuliano, Anna R.
Abstract: As oropharyngeal cancer (OPC) associated with human papillomavirus (HPV) increases in men, the need for a screening test to diagnose OPC early is crucial. While HPV‐associated OPC has a favorable prognosis, recurrence is likely, and metastatic OPC is often incurable regardless of HPV status. Our previous study of pretreatment, male OPC cases ( n = 101) and age‐ and smoking‐matched controls ( n = 101) found methylation of the host EPB41L3 tumor suppressor gene and HPV16 in the oral gargle was correlated with these biomarkers in the tumor. Methylation of these genes in the oral gargle was significantly ( p < 0.0001) higher among cases compared to controls. To further study the utility of HPV16/ EPB41L3 methylation, we expanded the sample size and specifically increased the number of early OPC cases (T1‐T2, N0‐N1; small tumors with a single ipsilateral node <3 cm) to evaluate these biomarkers in early and late OPC. This study included 228 OPC cases, 92 of which were early cases and frequency matched to 142 healthy controls. In logistic regression, the AUC for HPV16/ EPB41L3 methylation for all OPC cases was 0.82. Among early and late OPC cases, the AUC was 0.78 and 0.85, respectively. For early cases, 76% sensitivity was achieved, replicating results from our prior study, with a specificity of 65%, indicating room for improvement. The ability of HPV16/ EPB41L3 methylation to distinguish OPC from healthy controls highlights its utility as a potential biomarker for OPC. However, the inability to predict early OPC better than late stage OPC indicates the need for additional biomarkers to improve screening performance. Abstract : We have expanded our previous study with priority in increasing early OPC case sample size to specifically test the performance of HPV16/EPB41L3 methylation as a biomarker for early OPC detection. This study, like the prior study, found HPV16/EPB41L3 methylation as a marker for OPC. Additionally, it has shown the potential for HPV16 and EPB41L3 methylation as a key factor in early detection of OPC but with more biomarkers needed to optimize detection for early OPC.